Artificial Intelligence and Blended Learning (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This is a reprint of the Special Issue “Artificial Intelligence and Blended Learning: Challenges, Opportunities, and Future Directions” in the Technology-Enhanced Education section of the Education Sciences journal. The call for papers was open from November 2024 through the end of December 2025. The issue comprises eight papers—six research articles and two systematic reviews—covering a broad range of topics, including AI adoption among college students, AI readiness of pre-service teachers, prediction of segment access frequency in lecture archives, frameworks for AI-driven metaverse technologies, evaluation of the accuracy of an educational AI model, and analyses of subject-specialized chatbots. The systematic reviews focus on cybersecurity curricula and on the use of ChatGPT in teaching and learning.